Tratamento do ronco primário e Síndrome da Apneia/Hipopneia Obstrutiva do Sono (SAHOS): um novo campo de trabalho para o cirurgião-dentista - Binhardi, Tiago Della Rovere [UNESP] (2014)
The Primary Snoring and OSAHS are taking space in Brazil and in the world nowadays. Recently the treatment through oral appliances (OAs) hasgained importance on researchs which have proven the efficiency of the devices and dentists' correct positioning once facing this multidisciplinary problem. The most used and most studied today are the mandibular positioners, that have had significant developments in recent years. It's mechanism of action is based on mandibular advancement which pushes away the oropharynx's tissues and increases the muscle tone in the region, preventing these tissues collapse, causing OSAHS. They are indicated in cases of primary snoring and mild to moderate sleep apnea. Treatment efficiency is directly linked to the characteristics of OAs, as well as to the individual's ones. The correct evaluation of the patient is performed by clinical examination by the physician and dentist, beyond series of tests that will give us the coordinates if it is the best procedure or not. From this point, this option of using intraoral plates, opens the doors to a new modality in dentistry called sleep dentistry which is responsible for collecting the indications and contraindications of OAs and knowing how to correctly indicate, not forgetting the multidisciplinary treatment, seeking better quality sleep and, consequently, better quality of life for patients with the syndrome. This study aims to elucidate the care that the dentist must have to achieve success in this treatment modality